University of the Third Age at the Faculty of Health and Social Sciences, the University of South Bohemia - Tóthová, Valérie; Šemberová, Jana (Magyar Gerontológia, 2021)
The goal of the paper is to present almost 30 years of activities of the University of the Third Age at the Faculty of Health and Social Sciences, the history of which started in 1992. The first discipline called Care of Humans and their Health was opened by the University of South Bohemia in the academic year 1992/93. The elderly were offered an educational six-term health and social program, while three hours of direct lessons and two counseling sessions a week (“senior Thursday) were subsidized. The students had to sit for unmarked and marked examinations, and to process and defend a thesis at the end of their study. In July 1995, 28 graduates were awarded a certificate on an extramural education in a festive ceremony. The implementation of the discipline of Care of Humans and their Health confirmed that even a non—professional leisure-time education could be provided at an “academic” level. A comprehensive view of education enabled to identify areas that should be taken into consideration during the education of elderly adults. They include areas relating to computer and functional literacy, cultivation of leisure time, culture of the interpersonal mutuality, and the human being (looking for the sense of life and higher goals). In the course of the thirty-year history of the University of the Third Age many activities have developed and the conception has extended. The new educational subject called Man in Health, Disease and Distress was transformed into a two-stage program offering the choice of the length and type of the educational program. The option A represented the choice of an integral and topically closed discipline while the options B and C represented the choice of the educational demandingness and inclusion in the European educational program called SoLiLL: Self-Organized Learning in Later Life. Furthermore, a conception of an extending program called Quality of life in the Old Age and other programs were offered to the elderly living in our region. As a part of the project activities, the elderly were involved in the projects of Phare a Interreg IIIA. The conception of the University of the Third Age at the Faculty of Health and Social Sciences of the University of South Bohemia enables the applicants to complete an integral educational program, lecture blocks/cycles with various topics, and, at the same time, a unique research program called “Golden Path” focused on the Czech-Austrian border area can be completed. The uniqueness of the educational research program is evidenced by two translated monographs called “Wallern und Wallerer (Volary a Volarští - Volary citizens and Volary)“ and „Der Goldene Steig“ (Zlatá stezka – Golden Path) by the indisputably most important expert and researcher of the Golden Path, a historian living in Bavarian Waldkirchen.